Методологічні та науково-правові основи педагогічної освіти вищої педагогічної освіти в Київському університеті Св. Володимира та Ніжинській гімназії вищих наук княза Безбородька - Половко, Ірина Віталіївна (My University, 2010)
В статье исследуются методологические и научно-правовые основы высшего педагогического образования в Нежинской гимназии высших наук князя Безбородька и Киевском университете Св. Владимира в сфере учебных дисциплин и в области их методологического обеспечения в первой половине ХІХ в.

Methodological, scientiﬁ c and legal basis of higher pedagogical education in Bezborod’ko’s Nizhyn gymnasium of higher sciences and Kyiv University of St. Volodymyr in academic disciplines and their methodological support in the ﬁ rst half of the nineteenth century have been investigated in the article. Based on the analysis or regulations and archival materials the author makes conclusions that in the above mentioned schools disciplines, which served as a scientiﬁ c and legal basis for the preparation of teachers for the Kiev and Chernihiv provinces, were taught.
Keywords: вища педагогІчна освіта; Київський університет Св. Володимира; Ніжинська гімназія; методологічне забезпечення; высшее педагогическое образование; Киевский университет Св. Владимира; Нежинская гимназия; методологическое обеспечение; higher pedagogical education; Kiev University of St. Vladimir; Nezhinskaja gymnasium; methodological support